2023
DOI: 10.1097/rct.0000000000001431
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Gallbladder Lesions: What Can Positron Emission Tomography/Computed Tomography Add to the Conventional Imaging Approach?

Abstract: Objective: Incidental gallbladder lesions are common in imaging studies, although it is not always easy to discriminate benign lesions from gallbladder cancer with conventional imaging procedures. The present study aims to assess the capacity of positron emission tomography/computed tomography (PET/CT) with 2-[ 18 F]FDG to distinguish between benign and malignant pathology of the gallbladder, compared with conventional imaging techniques (contrast-enhanced CT or magnetic resonance imaging).Methods: Positron em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have tried several modalities for differentiating between benign and malignant lesions. Sabaté-Llobera et al (16) compared the use of positron emission tomography/computed tomography (PET/CT) with 2-[18F]FDG to distinguish between benign and malignant pathology of the gallbladder compared with conventional imaging techniques (CE-CT or magnetic resonance imaging) and found that conventional imaging classified more studies as inconclusive compared with PET/CT (17.0% and 7.5%, respectively), although both procedures showed a similar accuracy. In this regard, the cost-to-benefit for conventional imaging might be superior due to its greater availability in less developed regions and lower cost.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have tried several modalities for differentiating between benign and malignant lesions. Sabaté-Llobera et al (16) compared the use of positron emission tomography/computed tomography (PET/CT) with 2-[18F]FDG to distinguish between benign and malignant pathology of the gallbladder compared with conventional imaging techniques (CE-CT or magnetic resonance imaging) and found that conventional imaging classified more studies as inconclusive compared with PET/CT (17.0% and 7.5%, respectively), although both procedures showed a similar accuracy. In this regard, the cost-to-benefit for conventional imaging might be superior due to its greater availability in less developed regions and lower cost.…”
Section: Discussionmentioning
confidence: 99%
“…18 F-FDG PET-CT[ 54 , 55 ] or 18 F-FDG PET-MRI[ 28 ] must be performed before every intended major curative resection to exclude any occult metastatic lesion, which is not visible by the other imaging techniques, particularly in port-site metastases after laparoscopic cholecystectomy[ 29 ] and in ambiguous cases or at follow-up[ 12 , 31 , 56 ].…”
Section: Diagnosismentioning
confidence: 99%